2005
DOI: 10.1590/s0101-20612005000200022
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre teores de colesterol em filés de tilápias e níveis de óleo de linhaça na ração

Abstract: RESUMOO objetivo deste trabalho foi investigar o efeito de rações contendo diferentes níveis de óleo de linhaça no teor de colesterol e na composição centesimal (umidade, cinza, proteína e lipídios totais) de filés de tilápia. A determinação do colesterol foi realizada através de cromatográfica líquida de alta eficiência (CLAE). Esta metodologia foi avaliada no presente trabalho mostrando-se exata e precisa. Os teores de colesterol variaram de 58,3 a 75,5mg/100g de tecido muscular, sendo que a inclusão de óleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
2
1
0
2
Order By: Relevance
“…The moisture and ash percentages (Table 4) of the muscle tissues of the animals in the two treatments were close to the rates given by Simões 22 and Tonial 23 in their research on the tilapia muscle tissue. The CP rates at the end of the current experiment were close to those given in the study by Visentainer 24 in juvenile tilapia, with rates ranging between 19.8 and 20.9%.…”
Section: Discussionsupporting
confidence: 87%
“…The moisture and ash percentages (Table 4) of the muscle tissues of the animals in the two treatments were close to the rates given by Simões 22 and Tonial 23 in their research on the tilapia muscle tissue. The CP rates at the end of the current experiment were close to those given in the study by Visentainer 24 in juvenile tilapia, with rates ranging between 19.8 and 20.9%.…”
Section: Discussionsupporting
confidence: 87%
“…Sales and Sales [42] obtained energy values for P. squamosissimus (109 kcal / 100 g) and Prochilodus cearensis and Curimata sp (185 kcal / 100g both), in ponds and Souza et al [37] reported for the species Schizodon fasciatum, in Amazon waters, energy value of around 125.43 kcal / 100g, so it's all much higher, compared to the values found in this study for P. squamosissimus (87 kcal / 100g), Curimata sp (92 kcal / 100g), P. lacustris (100kcal / 100g) and S. dissimilis (81 kcal / 100g), this difference in results are probably associated with the nature of the investigated environment, confirming what Stansby [38] postulates when he states that the chemical composition does not vary only from species to species, but also between individuals of the same species, and Visentainer et al [45] stating that the analytical data greatly vary according to the age, sex, diet, genetics, type and time of nesting, the productive stage, size, migration, and season as well as environmental factors associated with variations in fish habitat.…”
Section: A Proximate Analysis and Statistical Eveluationsupporting
confidence: 69%
“…Several authors report that the fatty acid composition of muscle tissue reflects the fatty acid composition of the diet (Lee et al, 2003;DurazoBeltrán et al, 2003;Jobling and Bendiksen, 2003;Justi et al, 2003;Visentainer et al, 2005;Tid well et al, 2007). In freshwater fish, such as tilapia, it is expected that the content of omega-3 fatty acids is less than that in marine fish.…”
Section: Enzymatic Hydrolysis and Yield Of Fractionsmentioning
confidence: 99%